The parasite clearance curve. - White, N (BioMed Central, 2011)
Parasite clearance rates are important measures of anti-malarial drug efficacy. They are particularly important in the assessment of artemisinin resistance. The slope of the log-linear segment in the middle of the parasite clearance curve has the least inter-individual variance and is the focus of therapeutic assessment. The factors affecting parasite clearance are reviewed. Methods of presentation and the approaches to analysis are discussed.